Penentuan Rute Mobil Pengangkut Sepeda dalam Proses Rebalancing sebagai Vehicle Routing Problem - Mirani Oktavia (Faktor Exacta, 2018)
The use of bicycles facilitated by a college can be seen as one of the interesting phenomena because the campus is required to always ensure that the number of bicycles in each bicycle storage area (shelter) must return to normal when the beginning of the lecture starts every day. While the existence of the mobility process carried out by all stakeholders of the campus is very possible to occur the increation of bicycles in a shelter which also resulted in the reduction of bicycles in other shelters. Therefore, a method is needed to return the number of bicycles like the early morning according to the capacity of each shelter using the car that is transporting which is then called the rebalancing process of bicycle. In this study a model of the operational of the car carrier was designed during the rebalancing process. Therefore, information is needed on which shelter routes to visit and how many bicycles are moved from one shelter to another. This distribution problem is categorized as one form of vehicle routing problem (VRP) to minimize mileage of the car that is transporting of bikes.